PENGARUH TEMPORARY AND PERMANENT DIFFERENCE TERHADAP PERTUMBUHAN LABA DENGAN SMALL AND LARGE BOOK TAX DIFFERENCES SEBAGAI MODERASI - Zati Rizka Fadhila, 13.05.52.0227; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
Book Tax Difference occur due to differences between the financial reporting and tax reporting in terms of accounting principles, methods and accounting procedures, the recognition of income and expenses, as well as the treatment of income and expenses. Due to the emergence difference will cause earnings growth will be increased or decreased. The profit growth can be affected by the components that refer to IAS 46 regarding the income taxÂ and IAS 12 on income tax Deferred tax is caused by the presence of taxable temporary differences. The study aims to find temporary and permanent difference to the growth of small and large profits with book tax differences sebagail moderation. This research is a descriptive research. With a sample of companies manufacturing sector Textile & Garment Industry, Customers, Housewares, Plastic & Packaging, Pulp & Paper, Glass, Metal, and Cable 30 manufacturing companies listed on the Stock Exchange in 2013 to 2015. Data were analyzed using regression multiple linear models with interactions basis moderation. The results showed that the temporary difference and permanent difference significant negative effect on profit growth. With small and large book tax differences are moderating variable.Keywords: Temporary Difference, Permanent Difference, Small and Large Book Tax Differences, Profit Growth